Pembuatan Plastik Biodegradable dari Limbah Cair Pengolahan Singkong dengan Penambahan Propilen Glikol sebagai Plasticizer - Ivana Putri; Sri Benti Etika (Jurnal Periodic Jurusan Kimia UNP, 2022)
Cassava is a plant that used as a raw material for processing in many food industries in Indonesia. The results of this processing will produce cassava liquid waste. This cassava liquid waste can be used as raw material for making biodegradable plastics with the addition of propylene glycol as a plasticizer. Propylene glycol plasticizer was variated as much as 1 mL, 2 mL, 3 mL, 4 mL and 5 mL. The characterization test obtained a maximum value of 3 mL of propylene glycol plasticizer which has a tensile strength value of 68.24 N/mm2, an elongation percent of 42.04%, a maximum water content test and swelling test value of 5 mL which increases with the addition of a propylene glycol plasticizer. The value of biodegradation on the addition of 5 mL of plasticizer propylene glycol reached 76,789% on the 15th day. And the functional groups test of biodegradable plastics using FTIR, no other functional groups were found.